2022
DOI: 10.3390/a15030095
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Harvest Time of Apple Trees: An RNN-Based Approach

Abstract: In the field of agricultural research, Machine Learning (ML) has been used to increase agricultural productivity and minimize its environmental impact, proving to be an essential technique to support decision making. Accurate harvest time prediction is a challenge for fruit production in a sustainable manner, which could eventually reduce food waste. Linear models have been used to estimate period duration; however, they present variability when used to estimate the chronological time of apple tree stages. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…de Souza et al [6] proposed artificial neural networks (ANNs) for predicting banana harvest time. Furthermore, recurrent neural networks (RNNs) and convolutional neural networks (CNNs) have been adopted to predict crop harvest time [1,11]. However, ANNs and CNNs (more suitable for image data) cannot handle the pre-post relationship with the presentation of time series.…”
Section: Artificial Intelligence For the Crop Harvest Time Prediction...mentioning
confidence: 99%
See 2 more Smart Citations
“…de Souza et al [6] proposed artificial neural networks (ANNs) for predicting banana harvest time. Furthermore, recurrent neural networks (RNNs) and convolutional neural networks (CNNs) have been adopted to predict crop harvest time [1,11]. However, ANNs and CNNs (more suitable for image data) cannot handle the pre-post relationship with the presentation of time series.…”
Section: Artificial Intelligence For the Crop Harvest Time Prediction...mentioning
confidence: 99%
“…Making an accurate crop harvest time prediction is a challenge for sustainable agricultural management, but it could eventually decrease resource waste [1]. For harvest time prediction, previous studies have attempted to use statistical analyses to make predictions [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While departing from traditional polynomial regression architectures, these models retained similar input features, such as temperature and solar radiation accumulation. For instance, LSTM networks were employed in [18] to improve apple production, exhibiting a three-day error in the average harvest day prediction. In a similar context, a study [19] demonstrated the estimation of bok choy production using advanced feature selection techniques to reduce the number of training parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, an investigation into the relationship between temperature and fruit growth and the ripening stage of tomatoes revealed that the accelerating effect of temperature on fruit maturation varies with each stage (de Koning, 2000). Boechel et al (2022) also argued that predicting the harvest date of apples using a linear model with accumulated temperature as a variable is highly unreliable at specific stages and cannot adequately represent the phenomenon. Similar to tomatoes and apples, strawberries have different temperature sensitivities to maturity depending on the fruit growth and ripening stage; however, this has not been fully elucidated in previous studies.…”
Section: Introductionmentioning
confidence: 99%